2017
DOI: 10.5897/jcmr2017.0291
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and perceived barriers to post-operative pain management: Institution based cross sectional study

Abstract: Post-operative pain is a common problem after surgical procedure. Undertreated and uncontrolled post-operative pain reduce physical and social performance, impaired quality of life and patient dissatisfaction, delayed discharge, increased use of health care resources and high cost on their hospital stay. Even if the problem is vast, researches on the area lack adequate data. This study aimed to assess knowledge, attitude and perceived barriers to post-operative pain management among anesthetists in Addis Ababa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Overall, our study showed that the employees possess an overall satisfactory level of knowledge. The range of values and the mean value of 66% of correct answers are comparable to or even higher than the results of similar examinations with the staff of paediatric clinics (De Freitas et al, 2014; Von Lützau et al, 2011; Notejane et al, 2019; Salanterä et al, 1999) and other medical disciplines (Setegn et al, 2009; Visentin et al, 2001). This is surprising, since pain is not a major topic of the child psychiatry staff education.…”
Section: Discussionsupporting
confidence: 67%
“…Overall, our study showed that the employees possess an overall satisfactory level of knowledge. The range of values and the mean value of 66% of correct answers are comparable to or even higher than the results of similar examinations with the staff of paediatric clinics (De Freitas et al, 2014; Von Lützau et al, 2011; Notejane et al, 2019; Salanterä et al, 1999) and other medical disciplines (Setegn et al, 2009; Visentin et al, 2001). This is surprising, since pain is not a major topic of the child psychiatry staff education.…”
Section: Discussionsupporting
confidence: 67%
“…Even if 73% participants have received training related to POP assessment and treatment only 14% of them assess POP regularly and 87% our study participants didn't have a pain guideline or standard in their organization. Yosef et al has found lack of pain assessment tool, lack of management protocol, guideline and poor documentation as a barrier for post-operative pain management [ 37 ]. This idea also supported by the study in Hong Kong which showed having a postoperative pain management program designed in an evidence-based procedure in specific manner can reduce postoperative pain and improve patient satisfaction [ 38 ].…”
Section: Discussionmentioning
confidence: 99%